Housing and children's wellbeing and development: evidence from a national longitudinal study - Taylor, Matthew; Edwards, Ben (My University, 2012)
Very little is understood about the influence of housing on children's development in Australia. For example, a recent review of the literature on this issue (Dockery et al., 2010) suggested that: "there is noticeably a lack of empirical research conducted in Australia on the links between housing and child development" (p. 2). In this paper, we begin to fill the gap in the Australian evidence on the influences of housing on children's development, using national data from Growing Up in Australia: The Longitudinal Study of Australian Children (LSAC). Specifically, we examine the association between housing tenure, residential mobility, and housing stress on children's cognitive development and social-emotional functioning.
Family Matters
Keywords: Child Development -- Emotional; Life Events; Housing -- Conditions; Child Development -- Cognitive; Disadvantage, adversity and resilience; Childhood and child development; Housing; Life Events; Child Development; Emotional; Conditions; Cognitive; Dsiadvantage, adversity and resilience; Adversity and resilience; Childhood and child development